Below-Knee Amputation Resulting from an Arterial Thrombosis from Tourniquet Use in a Patient with Undiagnosed Factor V Leiden: A Case Report. Issue 1 (January 2020) - Hautala, Gavin; Liu, Boshen; Hamilton, David; Aneja, Arun; Moghadamian, Eric
Abstract : Case: A 38-year-old woman presented with previously undiagnosed factor V Leiden (FVL), who suffered a complete superficial femoral arterial thrombosis after tourniquet use during the surgical repair of one of her bilateral tibial plafond fractures. This patient's injury eventually resulted in a below-knee amputation. Conclusion: We recommend expanding hypercoagulable screening on patients with risk factors based on a detailed history and physical examination. We also recommend limiting or negating tourniquet use in patients with FVL or other hypercoagulable disorders.